Cervical Lift-up Basket Laminoplasty after Resection of Spinal Intramedullary Tumors: A Finite Element Analysis and Clinical Image Evaluation - NAITO, Kentaro; NAKANISHI, Yuta; TAKAMI, Toshihiro (Neurologia Medico-Chirurgica, 2022)
Although reconstructive laminoplasty is commonly performed after resection of spinal intramedullary tumors of the cervical spine, its biomechanical rigidity of laminoplasty framework remains unclear. The objective of this study was to examine the structural reliability of our unique method of cervical lift-up basket laminoplasty by using computed tomography (CT)-based finite element analysis (FEA) and clinical radiological evaluation. A finite element model of cervical laminoplasty was created based on CT images using FEA software. Cervical lift-up basket laminoplasty (Basket) was compared with the standard style of open-door basket laminoplasty (Open-door). Clinical subjects for radiological evaluation comprised 33 patients who underwent cervical lift-up basket laminoplasty after resection of spinal intramedullary tumors. An FEA-equivalent stress histogram showed that stress was moderately dispersed around the basket. Virtual displacement of the spinous process of the Basket model was equivalent to that of the Open-door model in any direction of posterior-to-anterior, right-to-left, or top-to-bottom force. In the clinical analysis, radiological data with a minimum postoperative period of 6 months were obtained in a total of 28 out of 33 patients. No patients underwent revision surgery because of implant-related complications. No significant differences in C2-C7 angle or cervical tilt angle were observed between pre- and postoperatively. The structural rigidity of cervical lift-up basket laminoplasty was equivalent to the open-door style on the FEA. Clinical radiological evaluation suggested that there were no serious adverse events associated with cervical laminoplasty, although the longer postoperative follow-up is mandatory.